2010
DOI: 10.3390/ijms11125323
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Effects of Cucurbitacin B in Breast Cancer Cells: Down-Regulation of the c-Myc/hTERT/Telomerase Pathway and Obstruction of the Cell Cycle

Abstract: Naturally occurring cucurbitacins have been shown to have anticancer, antimicrobial and anti-inflammatory activities. In this study, we determined the effects of cucurbitacin B extracted from the Thai herb Trichosanthes cucumerina L. on telomerase regulation in three human breast cancer cell lines (T47D, SKBR-3, and MCF-7) and a mammary epithelium cell line (HBL-100). Cell viability after treatment with cucurbitacin B, which is an active ingredient of this herb, was assessed. Telomeric Repeat Amplification Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 37 publications
(39 reference statements)
1
42
0
Order By: Relevance
“…Furthermore, it enhances the anticancer effects of clinical chemotherapeutic drugs: cisplatin, gemcitabine, methotrexate, docetaxel, and gemcitabine [9][10][11][12]. Documented results also demonstrate that Cuc B potently inhibits the proliferation of breast cancer cell lines both in vitro and in vivo [13][14][15][16][17]. Cuc B suppressed breast cancer cell growth by HER2/integrin signaling, which further led to inhibiting integrin-mediated cell survival through ILK1 and paxillin [14], by disruption of microtubule polymerization and disturbance of nucleophosmin/ B23 translocation [15], and by inhibiting Wnt signaling [18].…”
Section: Introductionmentioning
confidence: 80%
“…Furthermore, it enhances the anticancer effects of clinical chemotherapeutic drugs: cisplatin, gemcitabine, methotrexate, docetaxel, and gemcitabine [9][10][11][12]. Documented results also demonstrate that Cuc B potently inhibits the proliferation of breast cancer cell lines both in vitro and in vivo [13][14][15][16][17]. Cuc B suppressed breast cancer cell growth by HER2/integrin signaling, which further led to inhibiting integrin-mediated cell survival through ILK1 and paxillin [14], by disruption of microtubule polymerization and disturbance of nucleophosmin/ B23 translocation [15], and by inhibiting Wnt signaling [18].…”
Section: Introductionmentioning
confidence: 80%
“…1A - D). Previous studies reported significantly high IC50 of CuB in normal mammary epithelial cell lines as compared to SKBR3 breast cancer cells [36]. To confirm the non-toxic effects of CuB, we evaluated its toxicity in a normal human melanocyte epithelial (PIG1) cells.…”
Section: Resultsmentioning
confidence: 99%
“…As found in the other cucurbitacins, cucurbitacin B has been reported as the antiproliferative agent of breast cancer cells in vitro and in vivo [15] and can induce apoptosis in Bcap37 breast cancer cells [16]. Our previous work revealed that cucurbitacin B inhibits growth and telomerase activity in breast cancer cell lines (T47D, SKBR-3, and MCF-7) and the inhibitory effect was obviously seen in the estrogen receptor (ER)-negative breast cancer cells SKBR-3 [17]. It also inhibits hTERT and c-Myc protein expression.…”
Section: Introductionmentioning
confidence: 82%